Sensory, Microbiological And Chemical Assessment Of Cod (Gadus Morhua) Fillets During Chilled Storage As Influenced By Bleeding Methods - Nguyen, Minh Van; Karlsdottir, Magnea Gudrun; Adalheidur Olafsdottir; Arnljotur Bjarki Bergsson; Sigurjon Arason (Zenodo, 2013)
The effects of seawater and slurry ice bleeding methods on the sensory, microbiological and chemical quality changes of cod fillets during chilled storage were examined in this study. The results from sensory evaluation showed that slurry ice bleeding method prolonged the shelf life of cod fillets up to 13-14 days compared to 10-11 days for fish bled in seawater. Slurry ice bleeding method also led to a slower microbial growth and biochemical developments, resulting lower total plate count (TPC), H2S-producing bacteria count, total volatile basic nitrogen (TVB-N), trimethylamine (TMA), free fatty acid (FFA) content and higher phospholipid content (PL) compared to those of samples bled in seawater. The results of principle component analysis revealed that TPC, H2S-producing bacteria, TVB-N, TMA and FFA were in significant correlation. They were also in negative correlation with sensory evaluation (Torry score), PL and water holding capacity (WHC). : {"references": ["", "A. S. Duun, and T. Rustad, \"Quality changes during superchilled storage\nof cod (Gadus morhua) fillets,\" Food Chemistry, vol. 105, pp. 1067-\n1075, 2007.", "R. Simpson, S. Almonacid, C. Acevedo, and C. Cortes, \"Mathematical\nmodel to predict effect of temperature abuse in MAP systems applied to\nPacific Hake (Merluccius australis),\" Journal of Food Engineering, vol.\n26, pp. 413-434, 2003.", "O. O. Cyprian, K. Sveinsdottir, H. Magnusson, and E. Martinsdottir,\n\"Application of quality index method (QIM) scheme and effects of\nshort-time temperature abuse in shelf life of fresh water arctic char\n(Salvelinus alpinus),\" Journal of Aquatic Food Product Technology, vol.\n17, pp. 303-321, 2008.", "O. O. Cyprian, H. L. Lauzon, R. Johannsson, K. Sveinsdottir, S. Arason,\nand E. Martinsdottir, \"Shelf life of air and modified atmospherepackaged\nfresh tilapia (Oreochromis niloticus) fillets stored under\nchilled and superchilled conditions,\" Food Science & Nutrition, vol. 1,\npp. 130-140, 2013.", "H. L. Lauzon, H. Magnusson, K. Sveinsdottir, M. Gudjonsdottir, and E.\nMartinsdottir, \"The effect of brining, modified atmosphere and\nsuperchilling on the shelf life of cod (Gadus morhua) loins,\" Journal of\nFood Science, vol. 74, pp. M258-M267, 2009.", "T. Wang, K. Sveinsdottir, H. Magnusson, and E. Martinsdottir,\n\"Combined application of modified atmosphere packaging and\nsuperchilled storage to extend shelf life of fresh cod (Gadus morhua)\nloins,\" Journal of Food Science, vol. 73, pp. S11-S19, 2008.", "J. H. Sohn, H. Ushio, N. Ishida, M. Yamashita, M. Terayama, and T.\nOhshima, \"Effect of bleeding treatment and perfusion of yellowtail on\nlipid oxidation in post-mortem muscle,\" Food Chemistry, vol. 104, pp.\n962-970, 2007.", "W. Flechtenmacher, \"Bleeding of cod on board factory trawlers,\" Archiv\nFur Fischereiwissenschaft, vol. 26, pp. 53-56, 1975.", "M. P. Richards, and H. O. Hultin, \"Contribution of blood and blood\ncomponents to lipid oxidation in fish muscle,\" Journal of Agricultural\nand Food Chemistry, vol. 50, pp. 555-564, 2002.\n[10] A. Duran, U. Erdemli, M. Karakaya, and M. Tyilmaz, \"Effects of\nslaughter methods on physical, biochemical and microbiological quality\nof rainbow trout Oncorhynchus mykiss and mirror carp Cyprinus carpio\nfillets in pre-, in- or post-rigor periods,\" Fisheries Science, vol. 74, pp.\n1146-1156, 2008.\n[11] S. Mochizuki, Y. Norita, and K. Maeno, \"Effects of bleeding on postmortem\nchanges in the muscle of horse mackerel,\" Nippon Suisan\nGakkaishi, vol. 68, pp. 276-279, 1998.\n[12] J. Everse, and N. Hsia, \"The toxicities of native and modified\nhaemoglobins,\" Free Radical Biology & Medicine, vol. 22, pp. 1075-\n1099, 1997.\n[13] C. Faustman, Q. Sun, R. Mancini, and S. P. Suman, \"Myoglobin and\nlipid oxidation interactions: Mechanistic bases and control,\" Meat\nScience, vol. 86, pp. 86-94, 2010.\n[14] R. Scherer, P. R. Augusti, C. Steffens, V. C. Bochi, L. H. Hecktheuer, R.\nLazzari, J. Radunz-Neto, S. C. G. Pomblum, and T. Emanuelli, \"Effect\nof slaughter method on post-mortem changes of grass carp\n(Ctenopharyngodon idella) stored in ice,\" Journal of Food Science, vol.\n70, pp. C348-C353, 2005.\n[15] C. Urbieta, and R. Gines, \"Optimisation of slaughtering method in\ngilthead seabream (Sparus aurata). Industrial application in fish farms,\"\nCahiers Options Mediterraneennes, vol. 51, pp. 71-77, 2000.\n[16] H. Stone, and J. L. Sidel, \"Descriptive analysis,\" in Sensory Evaluation\nPractices, H. Stone, and J. L. Sidel, Eds. Amsterdam: Elsevier, 2004,\npp. 201-244.\n[17] J. M. Shewan, R. G. Macintosh, C. G. Tucker, and A. S. C. Ehrenberg,\n\"The development of a numerical scoring system for the sensory\nassessment of the spoilage of wet white fish stored in ice,\" Journal of the\nScience of Food and Agriculture, vol. 4, pp. 283-298, 1953.\n[18] ISO 8586, Sensory analysis general guidance for the selection, training\nand monitoring of assessors. Part 1: selected assessors. Geneva: The\nInternational Organization for Standardization, 1993.\n[19] B. Margeirsson, H. Magnusson, K. Sveinsdottir, K. L. Valtysdottir, E.\nReynisson, and S. Arason, The effect of different precooling media\nduring processing and cooling techniques during packaging of cod\n(Gadus morhua) fillets. Report No. 15/10, ISSN 1670-7192 by the\nMatis-Icelandic Food and Biotech R&D, Reykjavik, Iceland, 2010.\n[20] L. Gram, G. Trolle, and H. H. Huss, \"Detection of specific spoilage\nbacteria from fish stored at low (0 \u00b0C) and high (20 \u00b0C) temperatures,\"\nInternational Journal of Food Microbiology, vol. 4, pp. 65-72, 1987.\n[21] ISO 6496, Animal feeding stuffs - Determination of moisture and other\nvolatile matter content. Geneva: The International Organization for\nStandardization, 1999.\n[22] O. Eide, T. Borresen, and T. Strom, \"Minced fish production from\ncapelin (Mallotus villosus). A new method for gutting, skinning and\nremoval of fat from small fatty fish species,\" Journal of Food Science,\nvol. 47, pp. 347-354, 1982.\n[23] P. Malle, and M. Poumeyrol, \"A new chemical criterion for the quality\ncontrol of fish: Trimetylamine/Total volatile basic nitrogen (%),\"\nJournal of Food Protection, vol. 52, pp. 419-423, 1989.\n[24] E. G. Bligh, and W. J. Dyer, \"A rapid method of total extraction and\npurification,\" Canadian Journal of Biochemistry and Physiology, vol.\n37, pp. 911-917, 1959.\n[25] R. Lowry, and I. Tinsley, \"Rapid colorimetric determination of free fatty\nacids,\" Journal of the American Oil Chemists' Society, vol. 53, pp. 470-\n472, 1976.\n[26] M. Bernardez, L. Pastoriza, G. Sampedro, J. J. R. Herrera, and M. L.\nCabo, \"Modified method for the analysis of free fatty acids in fish,\"\nJournal of Agricultural and Food Chemistry, vol. 53, pp. 1903-1906,\n2005.\n[27] J. C. M. Stewart, \"Colorimetric determination of phospholipids with\nammonium ferrothiocyanate,\" Analytical Biochemistry, vol. 104, pp. 10-\n14, 1980.\n[28] K. Sveinsdottir, G. Hyldig, E. Martinsdottir, B. Jorgensen, and K.\nKristbergsson, \"Application of Quality Index Methods (QIM) scheme in\nshelf life study of farmed Atlantic salmon (Salmo salar),\" Journal of\nFood Science, vol. 6, pp. 1570-1579, 2002.\n[29] D. V. Green, \"Sensory evaluation of fish freshness and eating qualities,\"\nin Handbook of seafood quality, safety and health application, C.\nAlasalvar, F. Shahidi, K. Miyashita, and U. Wanasundara, Eds. Oxford:\nBlackwell Publishing Ltd, 2011, pp. 29-38.\n[30] E. Martinsdottir, K. Sveinsdottir, J. Luten, R. Schelvis-Smith, and G.\nHyldig, Sensory Evaluation of Fish Freshness. Reference Manual for the\nFish Sector. QIM-Eurofish, The Netherlands, 2001.\n[31] H. Magnusson, and E. Martinsdottir, \"Storage quality of fresh and\nfrozen-thawed fish in ice,\" Journal of Food Science, vol. 60, pp. 273-\n278, 1995.\n[32] P. Dalgaard, \"Qualitative and quantitative characterization of spoilage\nbacteria from packed fish,\" International Journal of Food Microbiology,\nvol. 26, pp. 319-33, 1995.\n[33] H. H. Huss, P. Dalgaard, and L. Gram, \"Microbiology of fish and fish\nproducts,\" in Seafood from producer to consumer; integrated approach\nto quality, J. B. Luten, T. Borresen, and J. Oehlenschlager, Eds.\nAmsterdam: Elsevier, 1997, pp. 413-430.\n[34] P. Dalgaard, L. Gram, and H. H. Huss, \"Spoilage and shelf-life of cod\nfillets packed in vacuum or modified atmospheres,\" International Journal\nof Food Microbiology, vol. 19, pp. 283-294, 1993.\n[35] L. Gram, and H. H. Huss, \"Microbiological spoilage of fish and fish\nproducts,\" International Journal of Food Microbiology, vol. 33, pp. 121-\n137, 1996.\n[36] A. Olafsdottir, B. Margeirsson, K. Sveinsdottir, S. Arason, E.\nReynisson, and E. Martinsdottir, Effect of superchilled processing of\nwhole whitefish-pre-rigor. Report No. 22/12, ISSN 1670-7192 by the\nMatis-Icelandic Food and Biotech R&D, Reykjavik, Iceland, 2012.\n[37] R. Ofstad, B. Egelandsdal, S. Kidman, R. Myklebust, R. L. Olsen, and\nA. M. Hermansson, \"Liquid loss as effected by post mortem\nultrastructural changes in fish muscle: Cod (Gadus morhua L.) and\nsalmon (Salmo salar),\" Journal of the Science of Food and Agriculture,\nvol. 71, pp. 301-312, 1996.\n[38] G. B. Olsson, R. Ofstad, J. B. L\u00f8demel, and R. L. Olsen, \"Changes in\nwater-holding capacity of halibut muscle during cold storage,\" LWTFood\nScience and Technology, vol. 36, pp. 771-778, 2003.\n[39] S. Wada, and Y. Ogawa, \"High pressure effects on fish lipid\ndegradation: Myoglobin change and water holding capacity,\" in High\npressure bioscience and biotechnology, R. Hayashi and C. Balny, Eds.\nAmsterdam: Elsevier, 1996, pp. 351-356.\n[40] J. J. Connell, Control of fish quality (4rd Ed.). Oxford: John Wiley &\nSons, 1995, pp. 122-150.\n[41] H. H. Huss, Quality and quality changes in fresh fish, FAO Fisheries\nTechnical Paper. No. 348. Rome, 1995.\n[42] M. Sivertsvik, \"Active packaging in practice: fish,\" in Novel food\npackaging techniques, R. Ahvenainen, Ed. Cambridge: Woodhead\nPublishing Limited, 2003, pp. 384-396.\n[43] G. Jin, J. Zhang, X. Yu, Y. Zhang, Y. Lei, and J. Wang, \"Lipolysis and\nlipid oxidation in bacon during curing and drying-ripening,\" Food\nChemistry, vol. 123, pp. 465-471, 2010.\n[44] M. V. Nguyen, K. A. Thorarinsdottir, G. Thorkelsson, A.\nGudmundsdottir, and S. Arason, \"Influences of potassium ferrocyanide\non lipid oxidation of salted cod (Gadus morhua) during processing,\nstorage and rehydration,\" Food Chemistry, vol. 131, pp. 1322-1331,\n2012.\n[45] M. J. Haas, \"Lipolytic Microorganism,\" in Compendium of methods for\nthe Microbiological Examination of Foods, F. P. Downes, and K. Ito,\nEds. Washington: American Public Health Association, 2001, pp. 175-\n180."]}